Diversity and Scientific Progress in the Information Systems Discipline - Farhoomand, Ali; Drury, Don H. (Communications of the Association for Information Systems, 2001)
The Information Systems (IS) discipline is over a third of a century old. It is a multidisciplinary field of study that covers areas related to the management, deployment, and use of information technology. In response to this extended reach and the growing needs and requirements of its stakeholders, the IS community successfully solidified its foundations through institutionalization and professionalization. However, in light of a complex patronage structure, undisciplined diversity, and unbounded eclecticism in scholarly activities, the progress of IS as a scientific discipline has been attenuated. Drawing lessons from the field of psychology, this paper calls for solidifying the disciplinary matrix of IS. It argues that scientific progress of IS can be advanced further through the development of cumulative and exemplary theories aimed at significant problems. Such a cumulative approach to research tradition and knowledge unification would help demarcate the boundaries of the IS domain not in terms of its subject matters, but by the theories it develops to solve the problems within its domain.